Visual echocardiographic scoring system of the left ventricular filling pressure and outcomes of heart failure with preserved ejection fraction. (25th October 2021) - Murayama, Michito; Iwano, Hiroyuki; Obokata, Masaru; Harada, Tomonari; Omote, Kazunori; Kagami, Kazuki; Tsujinaga, Shingo; Chiba, Yasuyuki; Ishizaka, Suguru; Motoi, Ko; Tamaki, Yoji; Aoyagi, Hiroyuki; et al.
Abstract: Aims: Elevated left ventricular filling pressure (LVFP) is a powerful indicator of worsening clinical outcomes in heart failure with preserved ejection fraction (HFpEF); however, detection of elevated LVFP is often challenging. This study aimed to determine the association between the newly proposed echocardiographic LVFP parameter, visually assessed time difference between the mitral valve and tricuspid valve opening (VMT) score, and clinical outcomes of HFpEF. Methods and results: We retrospectively investigated 310 well-differentiated HFpEF patients in stable conditions. VMT was scored from 0 to 3 using two-dimensional echocardiographic images, and VMT ≥2 was regarded as a sign of elevated LVFP. The primary endpoint was a composite of cardiac death or heart failure hospitalization during the 2 years after the echocardiographic examination. In all patients, Kaplan–Meier curves showed that VMT ≥2 ( n = 54) was associated with worse outcomes than the VMT ≤1 group ( n = 256) ( P < 0.001). Furthermore, VMT ≥2 was associated with worse outcomes when tested in 100 HFpEF patients with atrial fibrillation (AF) ( P = 0.026). In the adjusted model, VMT ≥2 was independently associated with the primary outcome (hazard ratio 2.60, 95% confidence interval 1.46–4.61; P = 0.001). Additionally, VMT scoring provided an incremental prognostic value over clinically relevant variables and diastolic function grading ( χ 2 10.8–16.3, P = 0.035). Conclusions: In patients with HFpEF, the VMT score was independently and incrementally associated with adverse clinical outcomes. Moreover, it could also predict clinical outcomes in HFpEF patients with AF. Graphical Abstract: